METODE MARKOV CHAIN DALAM PENGENDALIAN PERSEDIAAN UNTUK PERENCANAAN BIAYA PERSEDIAAN BAHAN BAKU PADA TOKO AIRIN BAKERY & CAKE SHOP - Putri Rahma Novia; Fibri Rakhmawati; Rima Aprilia (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
Airin Bakery & Cake Shop produces various kinds of cakes and bread. This shop is often faced with problems that occur, namely the supply of raw materials that are insufficient or excess so that the production process does not go well. This study aims to determine the ordering capacity and the right time to order raw materials to minimize the total cost of raw material inventory using the silver meal method. The total inventory cost is Rp. 14,637,947.4 less than the cost set by the company. Inventory control, which is a stochastic process, can also be carried out without regard to safety stock, lead time, and reorder points. The stochastic process of total inventory can be described by a finite number of states. The probability of transitions between these states is described by a markov chain. The markov chain method can predict future raw material inventory costs. After making several states on the amount of raw material inventory, a prediction of the future raw material inventory costs of Rp.31.747.932,98 is obtained